Blinding Measured: A Systematic Review of Randomized Controlled Trials of Acupuncture - Moroz, Alex (Hindawi Publishing Corporation, 2013)
Background. There is no agreement among researchers on viable controls for acupuncture treatment, and the assessment of the effectiveness of blinding and its interpretation is rare. Purpose. To systematically assess the effectiveness of blinding (EOB) in reported acupuncture trials; to explore results of RCTs using a quantitative measure of EOB. Data Sources. A systematic review of published sham RCTs that assessed blinding. Study Selection. Five hundred and ninety studies were reviewed, and 54 studies (4783 subjects) were included. Data Extraction. The number of patients who guessed their treatment identity was extracted from each study. Variables with possible influence on blinding were identified. Data Synthesis. The blinding index was calculated for each study. Based on blinding indexes, studies were congregated into one of the nine blinding scenarios. Individual study characteristics were explored for potential association with EOB. Limitations. There is a possibility of publication or reporting bias. Conclusions. The most common scenario was that the subjects believed they received verum acupuncture regardless of the actual treatment received, and overall the subject blinding in the acupuncture studies was satisfactory, with 61% of study participants maintaining ideal blinding. Objectively calculated blinding data may offer meaningful and systematic ways to further interpret the findings of RCTs.